Axiology of Anthropological Time in Stefan Furman’s Calendars of the 17th Century Gdansk - Krzysztofik, Małgorzata (Respectus Philologicus, 2014)
Time, as everybody knows, is the primary category of culture. Human’s altitude to the time determines how we see ourselves, the world and why we choose various activities. Entire scientific description of every culture has to contain characteristics of the specific time structure. One of the most important problems the answers to which we should search between texts of culture, is the axiology of the particular streams of the culture time. The article presents multifaceted characteristics of category of anthropological time in two calendars printed in Gdansk in the 17th century (for years 1652 and 1664). Questions about measure, pace, rhythm and axiology of human time are asked. The paper presents a discussion of typical characteristics of chronosophy of that epoch, anisotropy, which is a stream of many kinds of time flowing in parallel and in interaction with each other. The Christian concept of time which can be found in both calendars is decribed. Also rhythms of nature and culture (cycle of liturgical festivals) that regulate anthropological time are presented; how three dimensions of human experience of time (past, present, future) go together. Characteristics of axiological aspect of human time which has complex relations with numerous temporal structures and streams of time are given. Evidence that axiology of human time—oscillating between sacrum and profanum, between divine order and devil’s order, between human activity and God’s intervention – is given with regard to theological dimension in Stefan Furman’s calendariography as it is concentrated on reality out of this world. In theological perspective meaningful becomes the experience of earthly life, which gives every human being a chance to choose the good or the bad path of life, whilst they look for the redemption.